Relationship of physical distress to dizziness in patients with fibromyalgia. (2nd January 2016) - Sawada, Fusako; Nomura, Yasuyuki; Goto, Fumiyuki; Murakami, Masato; Jike, Maki; Toi, Teruo; Furusaka, Tohru; Ikeda, Minoru; Oshima, Takeshi
Abstract: Conclusions : The feelings of dizziness and unsteadiness of the patients with fibromyalgia supposed specifically amplified by the hypersensitivity mechanism of CSS (central sensitivity syndrome) of them. The severity of subjective pain and physical distress according to the questionnaires were not correlated with the objective body sway on the stabilometer. Objectives : Fibromyalgia manifests primarily as chronic pain of the entire body, but is also often associated with a variety of physical symptoms including dizziness and unsteadiness. This study assessed whether objective measures of body sway and unsteadiness of them are associated with their subjective dizziness findings. Method : Subjects were 24 patients diagnosed with fibromyalgia, but one patient who had the past history of sudden deafness was excluded. The 23 patients were assessed by a stabilometer as the objective measures of body sway, and JFIQ (Japanese version of the fibromyalgia impact questionnaire), DHI (dizziness handicap inventory) and ABC (activities-specific balance confidence) as the subjective questionnaires. Results : The significant correlations were shown between the scores of JFIQ and DHI, JFIQ and ABC, and DHI and ABC. Then, the body sway index of stabilometer environmental area was significantly correlated with DHI score. However, the stabilometer index was not correlated neither with JFIQ or ABC.